Upscaling Earth Material, Process, Catalyst - Heringer, Anna (gta Verlag, 2023)
Earth building is not only one of the oldest, but also one of the most modern construction methods of our time. What economic, environmental, and social conditions are necessary to make this building method more attractive? In the future, cement - the most important component of concrete - will, like other finite resources, become less viable to produce and significantly more expensive. Considering appropriate alternatives for building materials is imperative. This book presents a wide range of built and unbuilt projects as well as strategies for architecture using earth materials - a construction method that can be adapted to every culture and context. The authors give impressive examples to demonstrate groundbreaking technological innovations that highlight the advantages of this material, from its worldwide availability to its potential for complete recycling and climate-neutral production. The book also includes a focus on socially just implementation, in particular in emerging economies. This book reveals the incredible potential of earthen architecture - for people and for the entire planet.